Evidence and prospective of plant derived flavonoids as antiplatelet agents: Strong candidates to be drugs of future. (September 2018) - Khan, Harron; Jawad, Mohammad; Kamal, Mohammad Amjad; Baldi, Alessandra; Xiao, Jianbo; Nabavi, Seyed Mohammad; Daglia, Maria
Abstract: Platelets are involved in hemostasis, inflammation, and thrombosis processes. Following a vascular damage, the endothelium releases protein factors, allowing the adhesion of subendothelium to platelets. Then platelets are activated, leading to the secretion of biologically-active ligands including thromboxane A2, adenosine diphosphate and serotonin. Aspirin, clopidogrel and warfarin are the most common drugs used to meet the challenges of platelet aggregation. However, these agents face issues with aspirin resistance and bleeding. New therapeutically effective and safe agents are therefore strongly needed, and natural substances could be ideal candidates. Flavonoids, a chemically diverse group of polyphenols, might be important in this regard. Consumption of flavonoids is responsible for several health-promoting properties. A number of flavonoids have shown outstanding preclinical antiplatelet effects through various mechanisms. Flavonoids could provide an ideal approach as templates for new, clinically-effective and safe antiplatelet agents due to their inherent safety and multiple useful pharmacological hits. This review aims to report data from literature regarding flavonoids with antiplatelet activity, with a particular focus on possible mechanisms of action, pharmacokinetic profiles and overall safety, thus providing a strong rationale for the design of selective and well-directed antiplatelet agents of natural origin. Highlights: Flavonoids have shown outstanding preclinical antiplatelet effects through various mechanisms. Flavonoids could provide an ideal approach as templates for new antiplatelet agents. Flavonoids mechanisms of action, pharmacokinetic profiles and overall safety are reported.